Improving the Quality of Services for Rawalo Village Apparatus Through Information Technology Training and Assistance - Raden Sumantri; Deny Nugroho (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service journal aims to improve the quality of service in the Rawalo Village Apparatus through training and mentoring strategies in the application of information technology. Rawalo Village, as a government unit that is currently entering the digital era, needs to improve service quality to provide efficient and responsive services to the community. The research method used was technology training and assistance in Rawalo Village. The research results show that training and mentoring in the application of information technology significantly increases the competency of village staff in using the village information system. The application of information technology also has a positive impact on administrative efficiency and services to the community. In addition, public participation in utilizing digital services has increased significantly. this research makes an important contribution to understanding how training and mentoring in information technology can improve the quality of services at the village level. Recommendations are given for further development regarding sustainability of training, improving information technology infrastructure, and continuing to encourage active community participation in utilizing digital services to achieve better services in the Rawalo Village Apparatus